2017
DOI: 10.1016/j.nicl.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular shape and relative position abnormalities in preterm neonates

Abstract: Recent neuroimaging findings have highlighted the impact of premature birth on subcortical development and morphological changes in the deep grey nuclei and ventricular system. To help characterize subcortical microstructural changes in preterm neonates, we recently implemented a multivariate tensor-based method (mTBM). This method allows to precisely measure local surface deformation of brain structures in infants. Here, we investigated ventricular abnormalities and their spatial relationships with surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…The greatest consistency in preterm MD+ deviations was in the regions adjacent to the lateral ventricles, but even in this region only 13 of 82 infants showed significant abnormalities. Enlargement of the ventricles and alterations to their shape and relative position are often observed in preterm infants imaged at term-equivalent age ( Brouwer et al 2012 ; Paquette et al 2017 ). These, combined with other brain morphological alterations such as dolichocephalic head configuration ( McCarty et al 2017 ), might pose a certain challenge for image registration ( Mewes et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The greatest consistency in preterm MD+ deviations was in the regions adjacent to the lateral ventricles, but even in this region only 13 of 82 infants showed significant abnormalities. Enlargement of the ventricles and alterations to their shape and relative position are often observed in preterm infants imaged at term-equivalent age ( Brouwer et al 2012 ; Paquette et al 2017 ). These, combined with other brain morphological alterations such as dolichocephalic head configuration ( McCarty et al 2017 ), might pose a certain challenge for image registration ( Mewes et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 . With FIRST in the FMRIB Software Library (FSL), hippocampal structures were segmented in the MNI152 standard space ( Patenaude et al, 2011 ; Paquette et al, 2017 ) (see Fig. 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…41,43,47,48 The shape of the lateral ventricles has also been investigated extensively, with multiple studies classifying various lateral ventricular morphologies and rotational differences. 42,[51][52][53] The occipital horn of the lateral ventricle seems to be the most inconsistent portion, which can range from being completely absent to being present in variable lengths ( Fig 6B). 33,48,54 The temporal horn, especially the anterior tip, is also variable in shape but to a lesser extent compared with the occipital horn.…”
Section: Developmentmentioning
confidence: 99%
“…On the basis of the association of ventricular morphologic abnormalities due to underlying white matter damage, it has been suggested that mild ventricular asymmetries may be a sign of subtle white matter or deep gray matter abnormalities that may not be seen on imaging. Paquette et al 51 proposed that differences in the left lateral ventricle in preterm neonates may be related to subcortical white matter alterations, suggesting subcortical vulnerability to preterm birth. 42 Sadan et al 56 studied fetuses with normal-sized-but-asymmetric ventricles (defined as width of , 10 mm and a difference in width of .…”
Section: Developmentmentioning
confidence: 99%